Implementasi Evaluasi Pembelajaran Go Buya di MIS Istiqomah Perbatasan Entikong Kalimantan Barat - Pranata, Alvira; Syamsijulianto, Tri (Mafapress Institut Pesantren Mathali'ul Falah Pati, 2024)
Cultural literacy plays a crucial role in education, not only as an effort to protect and promote local and national cultural heritage, but also as a way to shape the identity of the Indonesian nation in society. This aims to ensure that love and preservation of cultural riches is maintained. MIS Istiqomah Entikong is located on the border between Indonesia and Malaysia. The aim of implementing the Go Buya Learning evaluation for students is to improve the quality of learning and develop insight into cultural literacy, and to see the implementation of Go Buya learning through learning media using educational and interactive games in accordance with student development whose results can be measured well. The strategy used in this research service activity is the Participatory Action Research (PAR) approach. The steps taken in this service activity are (1) conducting interviews with teachers and students at MIS Istiqomah Entikong regarding Go Buya Learning (2) Preparing materials and evaluation instruments in Go Buya learning (3) Making evaluation instruments for Go Buya learning and ( 4) Implementation of assistance for activities carried out from the observation stage, implementation process and overall evaluation of Go Buya learning.